2016
DOI: 10.1155/2016/8572601
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum-Aware Geographic Routing in Cognitive Vehicular Ad Hoc Network Using a Kalman Filter

Abstract: We propose a position-based routing protocol for cognitive radio vehicular ad hoc networks (CR-VANETs) using a Kalman filter algorithm. The protocol first selects an idle channel from among all the channels available to a vehicle while moving on a straight road and then finds the best relay node to deliver the packet to the destination. The selection of a relay node is done by dividing the vehicular transmission range into five regions, and then the source/relay node selects the one that is in the region havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Research, very similar to our research, is discussed in [28]. In this article, the authors suggest routing protocol for cognitive radio vehicular ad hoc networks (CR-VANETs) using a Kalman filter algorithm.…”
Section: Journal Of Computer Network and Communicationsmentioning
confidence: 56%
See 1 more Smart Citation
“…Research, very similar to our research, is discussed in [28]. In this article, the authors suggest routing protocol for cognitive radio vehicular ad hoc networks (CR-VANETs) using a Kalman filter algorithm.…”
Section: Journal Of Computer Network and Communicationsmentioning
confidence: 56%
“…But, the authors of [28] apply their methods to the original data set. This data set can have a very large volume.…”
Section: Journal Of Computer Network and Communicationsmentioning
confidence: 99%
“…We introduced four of them in the related work section. We call them SBGR, 17 Kalman-SGR, 18 MCTRPFS, 21 and SADTR 23 for short, respectively. The other two forwarding schemes are the adaptive quality-of-servicebased routing for VANETs (AQRV) 27 and the clustering-based reliable low-latency routing scheme for vehicular networks (CRLLR).…”
Section: Evaluation Metric and Comparison Objectmentioning
confidence: 99%
“…In their protocol, CR-enabled vehicles dynamically share TV-band channels to improve the relay selection efficiency and decrease the end-to-end delay. H Ghafoor and I Koo 18 propose a spectrum-aware geographic routing protocol to decrease the end-to-end delay in CR-VANETs. They employ the Kalman filter to predict the positions of all moving vehicles and reduce the delay of the network.…”
Section: Forwarding Schemes In Cr-enabled Vehicular Networkmentioning
confidence: 99%
“…Luo et al [5] showed that the spectrum band from 1 to 40 kHz is heavily shared among different acoustic users, triggering high competition to utilise the spectrum resource efficiently. Like the terrestrial radio spectrum [6], maritime communication systems [7] have also undergone spectrum scarcity due to the emerging demands of underwater applications.…”
Section: Introductionmentioning
confidence: 99%